A cutout isogeometric analysis for thin laminated composite plates using level sets. (1st September 2015) - Yin, Shuohui; Yu, Tiantang; Bui, Tinh Quoc; Xia, Shifeng; Hirose, Sohichi
Highlights: A novel NURBS-based isogeometric analysis is developed for structure behaviors with cutouts. The level sets are adopted for describing the cutouts. Trimmed NURBS surface is no longer required to describe the geometrical structure with cutouts. Eigenvalue and buckling analysis of thin cutout homogeneous and laminated plates is presented. Abstract: Numerical modeling with treatment of trimmed objects such as internal cutouts in terms of NURBS-based isogeometric analysis presents several challenges, primarily due to the tensor product of the NURBS basis functions. In this paper we develop a new simple and effective isogeometric analysis for modeling buckling and free vibration problems of thin laminated composite plates with cutouts. We adopt the classical plate theory for the present formulation. The new approach can nicely overcome the drawbacks in modeling complex geometries with multiple-patches as the level sets are used to describe the internal cutouts; while the numerical integration is used only inside the physical domain. Numerical examples with complicated shapes are considered and analyzed to show the influences of cutout geometry, fiber orientation, boundary conditions, etc. on natural frequency and buckling behaviors of laminated plates. The results are compared with reference solutions showing a high accuracy of the proposed method.